'A Serious menace to security': British intelligence, V.K. Krishna Menon and the Indian High Commission in London, 1947–52 - McGarr, Paul M. (Taylor & Francis (Routledge), 2010)
Recently released Security Service (MI5) documents offer new insights into the Indian government's vulnerability to communist subversion after 1947, and the extent to which this threatened British national security. Existing historical works have noted MI5's concern over the links between Indian nationalists and the Communist Party of Great Britain (CPGB) during the inter-war period. Absent from the current historiography, however, is an account of the British government's response to V. K. Krishna Menon's appointment as India's High Commissioner to the United Kingdom in 1947. This article examines the nature of Menon's relationship with the CPGB, the risk that communists working for him within India's High Commission posed to British security, and the strategy that MI5 developed to meet it. Taken as a whole, as this article illustrates, the Attlee government's conviction that India, and more particularly, Krishna Menon, represented a weak link in the Commonwealth security chain, opens up new perspectives on Anglo-Indian relations post-1947.